Ecological-geochemical evaluation of the state of surface water streams in the impact area of the tailing dump of the Urupsky Ore Mining - Gromova, V. A.; Shestakova, T. V.; Lipatnikova, O. A. (Moscow University geology bulletin, 2016)
Surface waters are subject to intense contamination with trace elements in ore mining areas. A complex study was performed for the state of waters and bottom sediments from the Bogachukha and Urup Rivers in the area of the abandoned tailing dump of the Urupsky Ore Mining. The impact exerted by the tailing dump on the concentration of elements in the water, suspended particulate matter, and bottom sediments of the rivers is evaluated. The major contaminants of surface waters and bottom sediments, as well as the forms of their element distribution are revealed.